Nature School as a Manifestation of Child-Friendly Schools in Madura Elementary Schools - Citrawati, Tyasmiarni; Supriyanto, Teguh; Suminar, Tri; Haryadi, Haryadi (Proceedings of International Conference on Science, Education, and Technology, 2024)
This study explores the implementation of Child-Friendly Schools (CFS) through the Nature School model in Madura. The aim is to identify the concrete steps taken by Nature Schools in realizing the principles of SRA and to identify the long-term benefits for child development derived from this approach. The qualitative research method with a case study of Excellentia Nature School in Madura was used, with data collected through in-depth interviews, participatory observations, and documentation from Nature Schools in Madura. The research findings show that Nature Schools in Madura have successfully created a safe, comfortable, and supportive learning environment for the holistic development of children by utilizing the natural environment as an open classroom, interactive learning methods, emphasis on character education, and active involvement of parents and the community. The benefits include increased motivation and academic achievement, positive character development, higher environmental awareness, and better physical and mental health. This study provides insights into best practices in implementing CFS through the Nature School approach and can serve as a reference for other schools wishing to adopt similar concepts.